2015
DOI: 10.1111/btp.12196
|View full text |Cite
|
Sign up to set email alerts
|

Birds, Cattle, and Bracken Ferns: Bird Community Responses to a Neotropical Landscape Shaped by Cattle Grazing Activities

Abstract: Large areas of tropical moist forests have been converted to cattle pastures, generating complex landscapes where different habitats are represented by small patches with an uneven spatial distribution. Here, we describe how bird communities respond to the different elements present in a livestock landscape that was originally dominated by tropical moist forest. We surveyed six habitats: open pastures, pastures with shrubs, early‐ and middle‐secondary forests, mature forest, and pastures invaded by bracken fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
1
7
1
1
Order By: Relevance
“…On the other hand, there was a high dominance in the early and mature stages compared to the intermediate stage. Different studies showed that in the early stage this is a typical pattern, where species associated to this stage reach high abundance values in relation to other species [43], as it was the case of the resident species Aphelocoma coerulescens and a migratory one, Regulus calendula. In mature forest, the dominance is not a common pattern, but in our study area, this result can be explained by the presence of resident species that were observed actively during the nesting period (March-April), such as Trogon mexicanus and…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, there was a high dominance in the early and mature stages compared to the intermediate stage. Different studies showed that in the early stage this is a typical pattern, where species associated to this stage reach high abundance values in relation to other species [43], as it was the case of the resident species Aphelocoma coerulescens and a migratory one, Regulus calendula. In mature forest, the dominance is not a common pattern, but in our study area, this result can be explained by the presence of resident species that were observed actively during the nesting period (March-April), such as Trogon mexicanus and…”
Section: Discussionmentioning
confidence: 90%
“…Los datos de riqueza y abundancia de especies de aves por sí solos no reflejan la intensidad de la perturbación en el paisaje. Sin embargo, las curvas de rango/abundancia nos permitieron visualizar la respuesta de las comunidades de aves a las modificaciones en el ambiente (MacGregor-Fors & Schondube, 2012;Maya-Elizarrás & Schondube, 2015). De esta manera, las especies más abundantes dentro del estudio fueron el tirano dorso negro seguido del loro cachete amarillo, del perico pecho sucio y del luis gregario, especies que generalmente están asociadas a hábitats abiertos, suburbanos o cultivos; es decir, hábitats que ya presentan cierto grado de perturbación.…”
Section: Discussionunclassified
“…Traditional rarefaction calculates the expected number of species by reducing the samples to a standard size, that is, to the lower number of individuals, or to the same number of samples in sample‐based rarefaction (Gotelli & Colwell ). For example, Maya‐Elizarrarás and Schondube () used rarefaction curves to compare the species richness of resident birds in a landscape shaped by cattle grazing and applied a cut‐off point to an equal number of individuals based on the habitat with the lowest sampled bird abundance. They found that cattle pasture sites invaded by bracken ferns, and pastures under use (open and colonized by shrubs), had lower species richness than did intermediate secondary forests and mature forest remnants.…”
Section: Current Methods For the Analysis Of Tropical Species Diversitymentioning
confidence: 99%